Nitrification and aerobic denitrification in anoxic-aerobic sequencing batch reactor - Alzate Marin, Juan Carlos (2016)
The aim of this study was to evaluate the feasibility of achieving nitrogen (N) removal using a lab-scale sequencing batch reactor (SBR) exposed to anoxic/aerobic (AN/OX) phases, focusing to achieve aerobic denitrification. This process will minimize emissions of N2O greenhouse gas. The effects of different operating parameters on the reactor performance were studied: cycle duration, AN/OX ratio, pH, dissolved oxygen concentration (DOC), and organic load. The highest inorganic N removal (NiR), close to 70%, was obtained at pH=7.5, low organic load (440mgCOD/(Lday)) and high aeration given by 12h cycle, AN/OX ratio=0.5:1.0 and DOC higher than 4.0mgO2/L. Nitrification followed by high-rate aerobic denitrification took place during the aerobic phase. Aerobic denitrification could be attributed to Tetrad-forming organisms (TFOs) with phenotype of glycogen accumulating organisms using polyhydroxyalkanoate and/or glycogen storage. The proposed AN/OX system constitutes an eco-friendly N removal process providing N2 as the end product.